2014
DOI: 10.1108/nbri-09-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Blaming leaders for team relationship conflict? The roles of leader-member exchange differentiation and ethical leadership

Abstract: Purpose – The purpose of this paper is to extend our understanding of the role of leaders in team relationship conflict. Leader-member exchange (LMX) differentiation was hypothesized to be positively related to team relationship conflict. Additionally, ethical leadership was hypothesized to moderate relations between LMX differentiation and team relationship conflict. Design/methodology/approach – Hypotheses were examined in a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Overall, the greater the LMX variation, the higher was the team conflict. Such a notion is supported by a recent study by Zhou and Shi (2014) which found that high LMX variation was associated with increased relationship conflict. Cobb and Lau (2015) also found that LMX variation had a negative effect on team conflict.…”
Section: Lmx Variationmentioning
confidence: 67%
“…Overall, the greater the LMX variation, the higher was the team conflict. Such a notion is supported by a recent study by Zhou and Shi (2014) which found that high LMX variation was associated with increased relationship conflict. Cobb and Lau (2015) also found that LMX variation had a negative effect on team conflict.…”
Section: Lmx Variationmentioning
confidence: 67%
“…Specifically, the literature on LMX differentiation (i.e., variance in reported LMX within teams; e.g., Li & Liao, 2014) has been instrumental in documenting this phenomenon. Although there is some inconsistent evidence on its effects (Martin et al, 2018), LMX differentiation has been found to increase relationship conflict (Chen, He, & Weng, 2018; Cobb & Lau, 2015; Zhou & Shi, 2014), which has been shown repeatedly to attenuate group performance (De Drue & Weingart, 2003; de Wit, Greer, & Jehn, 2012; O’Neill, Allen, & Hastings, 2013). Similarly, LMX differentiation has been found to attenuate cohesion in groups (Chen et al, 2018), which is critical to facilitating team performance (Beal, Cohen, Burke, & McLendon, 2003; Carron, Colman, Wheeler, & Stevens, 2002; Castaño, Watts, & Tekleab, 2013; Chiocchio & Essiembre, 2009; Evans & Dion, 1991; Gully, Devine, & Whitney, 1995; Mullen & Cooper, 1994).…”
Section: Lmx Lmx Differentiation and Group Cohesionmentioning
confidence: 99%
“…At the collective level, these relational boundaries within teams (“us” and “them”) are not desirable because a high LMX separation may elicit tensions and relational conflicts (Buengeler et al, 2021; Zhou & Shi, 2014) as well as reduce performance (Sui et al, 2016). We argue that high RLMX team members are more likely to experience energizing emotions, such as pride or gratitude, when LMX differentiation is high because this context signals that these employees are treated better than the other group by the leader.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%